An extended variational principle for non-linear and non-potential potentializable operators - Oliveira, Antonio Marmo; Boruszewski, Wolodymir (Revista Ciências Exatas, 2008)
For non-conservative mechanical systems (non-potential operators), classical energetic variational principles do not hold true. In this article, a generalized variational principle, valid for non-linear and non-conservative systems is deduced by means of “potentializable” operators. A systematic inclusion of boundary conditions in problems dealing with such operators is proposed and examples from continuum mechanics are presented.